2017
DOI: 10.3389/fmicb.2017.00641
|View full text |Cite
|
Sign up to set email alerts
|

Okara: A Nutritionally Valuable By-product Able to Stabilize Lactobacillus plantarum during Freeze-drying, Spray-drying, and Storage

Abstract: Okara is a nutritionally valuable by-product produced in large quantities as result of soymilk elaboration. This work proposes its use as both culture and dehydration medium during freeze-drying, spray-drying, and storage of Lactobacillus plantarum CIDCA 83114. Whole and defatted okara were employed as culture media for L. plantarum CIDCA 83114. The growth kinetics were followed by plate counting and compared with those of bacteria grown in MRS broth (control). No significant differences in plate counting were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Dehydrated okara contains about 9-10% humidity, 21% proteins, 55% whole fiber, 1.5% ash and 13-14% fats and oils (Quintana, Gerbino, & Gomez-Zavaglia, 2017). Because of the nutritional value of its components (proteins of high nutritional value, dietary fiber, antioxidants, unsaturated lipids), okara appears as a valuable source of different ingredients for the formulation of functional foods (Vong & Liu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dehydrated okara contains about 9-10% humidity, 21% proteins, 55% whole fiber, 1.5% ash and 13-14% fats and oils (Quintana, Gerbino, & Gomez-Zavaglia, 2017). Because of the nutritional value of its components (proteins of high nutritional value, dietary fiber, antioxidants, unsaturated lipids), okara appears as a valuable source of different ingredients for the formulation of functional foods (Vong & Liu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The structural study of okara flour was previously investigated using various techniques, including scanning electron microscopy (SEM; Porcel et al, ; Voss et al, ; Santos et al, ) and Fourier transform infrared (FTIR) spectroscopy (Kamble et al, ; Li et al, ; Quintana, Gerbino, & Gómez‐Zavaglia, ). SEM is a useful technique for determining the microstructure of food products by evaluating the arrangement of starch granules within the protein matrix (Kamble et al, ).…”
Section: Structural Characteristics Of Okaramentioning
confidence: 99%
“…FTIR spectroscopy may show structural similarities or differences between samples based on the presence or absence of specific functional groups (Rani, Singh, Kamble, Upadhyay, & Kaur, ). Quintana et al () studied the FTIR spectra of frozen whole and defatted okara specimens in the 4,000–500 cm −1 wavelength range. FTIR spectrum of frozen okara showed the existence of bands of lipids and carbohydrates.…”
Section: Structural Characteristics Of Okaramentioning
confidence: 99%
“…Despite the increased interest in antioxidant and prebiotic components naturally present in fruit processing coproducts [5,18], studies on the protective effects of these materials on probiotic cells during exposure to dehydration processes are scarce. Only one previous study reported the stabilizing effects of okara, a coproduct from soy milk elaboration, on Lactobacillus plantarum during freeze-drying [19]. Considering these aspects, this study evaluated whether coproducts generated during the processing of acerola, cashew, and guava can exert protective effects on probiotic Lactobacillus strains during freeze-drying and storage.…”
Section: Introductionmentioning
confidence: 99%